COVID-19 infection risk in pakistani health-care workers: The cost-effective safety measures for developing countries - Norina Usman; Mohammed A Mamun; Irfan Ullah (Wolters Kluwer Medknow Publications, 2020)
To combat the massive COVID-19 infection rates, the health-care workers (HCWs) are likely to work for long hours under substantial pressures, along with the infection risk. The consequence is that the HCWs become progressively hesitant to their works and psychologically impaired. In developing countries such as Pakistan, the health-care facilities are limited; hence, the HCWs safety measures are a great concern. Thus, these country needs a cost-effective strategy focusing on sympathetic discussions, that can be beneficial to reduce the psychological sufferings by ensuring the protection of the HCWs to facilitate proper services in combating with the COVID-19 crisis- which is provided in this commentary.